Prevalence and associated risk factors of type 2 diabetes mellitus among obstructive sleep apnoea patients / Muhammad Amin Ibrahim - Ibrahim, Muhammad Amin (2015)
There is a high prevalence of type 2 diabetes mellitus (T2DM) among obstructive sleep apnoea (OSA) patients; however the definite association between T2DM and other cardiovascular (CV) risk factors among OSA patients are not established. This study aims to determine the prevalence and associated risk factors of T2DM among OSA patients. Methodology: A cross-sectional study from an OSA database in UiTM multidisciplinary sleep clinic between 1st January 2010 and 31st December 2014. Demographic and anthropometric indices, polysomnographic studies, cardiovascular risks-type2 diabetes mellitus, hypertension and dyslipidaemia, blood pressure readings and metabolic profiles (fasting plasma glucose, glycated haemoglobin, triglycerides and high-density-lipoprotein levels) were reviewed. Results: A total of 183 OSA patients were included in this study. The prevalence of T2DM is 49%, obesity is 91%, hypertension is 78% and dyslipidaemia is 67%. OSA patients with T2DM were associated with older age (54.5 vs. 47.2 years old, p 0.001), higher body mass index (38.2 vs. 35.8 kg/m , p 0.041) and higher systolic blood pressure (140 vs. 132 mmHg, p 0.01) in comparison to OSA patients without T2DM. In multivariate analysis, OSA patients with T2DM were associated with older age OR 1.04 (1.01- 1.07), higher BMI OR 1.005 (1.001-1.099), hypertension OR 4.2 (1.3-13.9) and dyslipidaemia OR 4.9 (2.1-11.4). Conclusion: The prevalence of T2DM among OSA patients was high and it was associated with older age, a higher body mass index, hypertension and dyslipidaemia. Therefore, screening for T2DM is recommended for all patients diagnosed with OSA